2018
DOI: 10.1177/0013161x18785871
|View full text |Cite
|
Sign up to set email alerts
|

A View From the Top: Superintendents’ Perceptions of Mental Health Supports in Rural School Districts

Abstract: A chasm exists between the expanding mental health needs of school-aged youth and the school resources available to address them. Education agencies must efficiently allocate their limited resources by adopting innovative public health models. The need for these effective approaches is acute in rural regions, where resources tend to be scarce. This mixed-methods study of school superintendents illuminates key opportunities to optimize access to care for students struggling with mental health needs in rural com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 46 publications
2
39
0
1
Order By: Relevance
“…It should be noted that one mixedmethods study had a low response rate. 26 Nevertheless, the authors highlighted this is comparable to other online survey-based studies and that respondents were from a small population (i.e. superintendents in rural California school districts).…”
Section: Study Qualitysupporting
confidence: 63%
See 1 more Smart Citation
“…It should be noted that one mixedmethods study had a low response rate. 26 Nevertheless, the authors highlighted this is comparable to other online survey-based studies and that respondents were from a small population (i.e. superintendents in rural California school districts).…”
Section: Study Qualitysupporting
confidence: 63%
“…Articles reviewed came from 3 countries-3 from the USA 22,23,26 one from Australia 27 and one from the UK. 28 One article included data from a regional location 27 and 4 from rural areas.…”
Section: Locationmentioning
confidence: 99%
“…Compared with research focused on urban and suburban settings, research on educational leadership in rural school districts is a relatively small and somewhat dated body of research. One review of literature focused on rural education, found that between 1991 and 2003 issues related to educational leadership were addressed less frequently in the rural literature than studies focused on programs for students with special needs as well as research examining instruction, school safety, predictors of academic achievement, and students' attitudes or behaviors (Arnold et al, 2005;O'Malley et al, 2018). More recently, Preston et al (2013) reviewed published research from 2003 to 2013.…”
Section: Research On Rural Educational Leadershipmentioning
confidence: 99%
“…I artiklar studeras skolledares praktik på grundval av etnicitet och ras (Gándara & Aldana, 2014;Davis, Gooden & Micheaux, 2015;Green, 2015;Wilson, 2016;Murakami, Hernandez, Mendez-Morse & Byrne-Jimenez, 2016;DeMatthews, Carey, Olivarez & Moussavi Saeedi, 2017;Green, 2017;Truong & Hallinger, 2017;Zembylas & Iasonos, 2017;Johnson & Pak, 2018;Irby, 2018;Brooks & Brooks, 2018). Här finns också studier som undersöker lhbtq-frågor relaterade till ledarskap (O'Malley & Capper, 2015;Galloway & Ishimaru, 2015;Lewis & Kern, 2018) samt ledarskap i glesbygd (O'Malley, Wendt & Pate, 2018;Hardwick-Franco, 2018). Temat kännetecknas också av artiklar med ett renodlat fokus på ledarskap utifrån ett socialt rättviseperspektiv (DeMatthews, 2018;DeMatthews, Edwards Jr & Rincones, 2016;Moral, Garcia-Garníca & Martínez-Valdivia, 2018;Wang, 2018).…”
Section: Värderingar Etik Och Likvärdighetunclassified